Возрастная чувствительность грызунов к зооцидам - Пегельман, С.Г. (Вестник зоологии, 1976)
As a result of the author's own experimental studies and generalization of the data from literature the difference is found in reaction of rodents of different age groups to certain zoocides used in argiculture. It is established that age sensitivity of rodents of various species with respect to the same preparation may be absolutely different.